Fat metabolism in exercise - with special reference to training and growth hormone administration - Lange, K. H. W. (Scandinavian Journal of Medicine & Science in Sports, 2004)
Despite abundance of fat, exclusive dependency on fat oxidation can only sustain a metabolic rate corresponding to 50-60% of VO2max in humans. This puzzling finding has been subject to intense research for many years. Lately, it has gained renewed interest as a consequence of increased obesity and physical inactivity imposed by Western lifestyle. Why are humans so poor at metabolizing fat? Can fat metabolism be manipulated by exercise, training, diet and hormones? And why is fat stored in specialized adipose tissue and not just as lipid droplets inside muscle cells? In the present review, human fat metabolism is discussed in relation to how human fat metabolism is designed. Limitations in this design are explored and examples of different designs for fat metabolism from animal physiology are included to illustrate these limitations. Various means of manipulating fat metabolism are discussed with special emphasis on exercise, training, growth hormone (GH) physiology and GH administration. It is concluded that fat stores, non-esterified fatty acids (NEFAs) availability and enzymes for fat oxidation can be increased substantially. However, it is almost impossible to increase fat oxidation during endurance exercise at higher intensities. It seems that, for some reason, the human being is far from optimally designed for fat oxidation during exercise. Acute GH administration has several unexpected effects on fat and carbohydrate metabolism during aerobic exercise, and future research in this area is likely to provide valuable information with respect to GH physiology and the regulation of fat and carbohydrate metabolism during aerobic exercise.